Tax Aggressiveness and Corporate Transparency - Balakrishnan, Karthik; Blouin, Jennifer L.; Guay, Wayne R. (The Accounting Review, 2019)
ABSTRACT We investigate whether aggressive tax planning firms have a less transparent information environment. Although tax planning provides expected tax savings, it can simultaneously increase the financial complexity of the organization. And to the extent that this greater financial complexity cannot be adequately clarified through communications with outside parties, such as investors and analysts, transparency problems can arise. Our investigation of the association between tax aggressiveness and information asymmetry, analysts' forecast errors, and earnings quality suggests that aggressive tax planning is associated with lower corporate transparency. We also find evidence that managers at tax-aggressive firms attempt to mitigate these transparency problems by increasing various tax-related disclosures. Overall, our results suggest that firms face a trade-off between tax benefits and financial transparency when choosing the aggressiveness of their tax planning. JEL Classifications: G30; H26; M41.